Design and fabricate an automatic fish feeder - Chan, See Ling (2009)
The objectives of this thesis are to design and fabricate a low cost and longer life span automatic fish feeder. This automatic fish feeder is designed to dispense food into the aquarium at a particular time each day. In this project, concepts are generated through the research on the existing patents to improve its limitations. Water power is used as the main mechanism to design this fish feeder. To accomplish the factors of lost cost and longer life span, water wheel is used to transmit the input power from water. In this concept, a water wheel connected with the food container by a shaft. The water from aquarium filter is drip into a rotatable water container with a constant rate. A valve is used to control the flow of water that drip into the rotatable water container. The container empties the water by drop on the water wheel when it is pivoted by the weight of the water. The water wheel is rotating once the water flow through it. A rotational movement of water wheel cause the food container rotates and dispenses the food from a small hole.